363 Relationship Between Parasite Load and Performance in Goat Kids at Weaning and Early Post Weaning. (8th October 2021) - Adeyemi, James; Andries, Kenneth; Clement, Emily
Abstract: Goats are small ruminants that have enormous potential to boost the economy and be a major source of income especially to marginal farmers and landless laborers. A very common and economically important condition, which affects domestic livestock species worldwide, is Gastrointestinal (GI) parasitism. Haemonchus contortus is the gastrointestinal parasite most common in small ruminants. To better understand the impact of GI parasitism, a study was conducted to research the relationship between parasite load and performance in goat kids at weaning and 60 d post-weaning. Fecal samples were collected at weaning and 60 d post-weaning and egg counts were performed using the modified McMasters technique. Data collected included weights, Fecal Egg Count at weaning, and at 60 d post-weaning. The average fecal egg count at weaning was 830 eggs per gram and 1103 eggs per gram 60 d post-weaning for H. contortus. Egg count at weaning was significantly related to weight at both weaning and 60 d post-weaning (P < .0001 and P = .0003 respectively), but not to ADG (P > .05). Fecal egg count at 60 d post-weaning was not significantly related to either weight or ADG (P > .05). Egg counts at weaning and 60 days post-weaning were not related (P = .0708). The results indicate that early parasite infection can influence animal weights. The lack of a significant correlation between egg counts at weaning and 60 d post weaning indicates a need to evaluate parasite load at later ages in kids when selecting for resistance.